Strongly Unforgeable and Efficient Proxy Signature Scheme with Fast Revocation Secure in the Standard Model - Liaojun Pang; Huiyang Zhao; Xia Zhou; Huixian Li (International Journal of Distributed Sensor Networks)
The existing proxy signature schemes with the proxy revocation function are proven to be malleable and do not possess strong unforgeability. Motivated by these concerns, a new proxy signature scheme with fast revocation is proposed, and it can be proved that the proposed scheme can achieve strong unforgeability in the standard model. By using this scheme, the original signer can generate the delegation warrant for the proxy signer, and at the same time, he/she can perform the immediate revocation to completely terminate the delegation when needed. Analyses show that the proposed scheme satisfies all of the security requirements of proxy signature and has shorter public parameters than the existing ones.